Does a relationship exist between hamstring flexibility and balance scores in female collegiate athletes? - Johns, N.; Mastromonaco, K.; Melton, M.; Shim, A.; Waller, M. (The Journal of Strength and Conditioning Research, 2021)
Introduction: The hamstring muscles play an important role as a prime mover, stabilizer, and providing proprioceptive information (1,3). The majority of collegiate athletes have been taught to improve hamstring flexibility to reduce their risk for injuries and improve sport performance. However, when performing a postural task in sport activities, these afferent and efferent fibers contribute towards muscle movement with the help of mechanoreceptors to assist with balance coordination (2,3). There have been several studies focusing on the importance of balance control with proprioceptive connective tissues but very few have tested hamstring flexibility directly. Therefore, the purpose of this study was to determine if hamstring flexibility has an association with balance scores among female college athletes. Methods: 15 healthy female college athletes (age 22.66 ± 0.87, height 174.77 ± 4.12 cm, mass 76.56 ± 9.17 kg, body mass index 23.06 ± 2.75) from a Midwest institution volunteered to participate in this study. All subjects qualified by being a college athlete, filling out a health questionnaire demonstrating good health, and signed informed consents and were without injury to the hamstring muscles. Each subject were assessed hamstring flexibility by using a goniometer in the supine position. 3 measurements were taken and the average was recorded. Center of Pressure (CoP) scores were measured with the eyes open stable surface (EOSS), eyes closed stable surface (ECSS), eyes open perturbed surface (EOPS), and eyes closed perturbed surface (ECPS) using a Bertec Computerized Posturography Plate (Columbus, OH). Results: A Pearson correlation (SPSS v. 24) showed weak correlations between (EOSS r = 0.022; ECSS r = 0.081; EOPS r = 0.181; ECPS r = 0.074) static balance scores and hamstring flexibility. Conclusions: Based on the current results it appears hamstring flexibility does not influence static balance scores. Further studies could look at dynamic balance scores (Limit of Stability) and hamstring flexibility since athletes tend to be moving when contracting the lower limb prime movers.